GIS-material for the archaeological project: Stone Age remains in Ledberg - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to local planning within Ledberg 10:1, Ledberg parish, Linköping municipality, the Swedish National Heritage Board's Contract Archaeology Division, UV Öst, has performed an archaeological assessment, stage 2, to examine whether the area contains any archaeological remains. In the mid part of the survey area. six hearths and post holes were found, as well as worked quartz and fire cracked stones. The features probably date to the Stone Age. The area with distinct archaeological remains was almost completely delimited. The rest of the survey area only contained occasional traces of prehistoric activity.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the assessment was to examine whether the area contains any unmarked archaeological remains.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
På grund av arbete med ny detaljplan inom Ledberg 10:1, Ledbergs socken, Linköpings kommun har UV Öst utfört en arkeologisk utredning etapp 2 för att konstatera om området innehåller omarkerade fornlämningar. I undersökningsområdets mellersta del påträffades 6 härdar och stolphål samt bearbetad kvarts och mindre skärvstenar. Anläggningarna härrör troligen från stenålder. Fornlämningsområdet med tydliga anläggningar kunde i det närmaste avgränsas och på övriga delar av utredningsområdet fanns endast något enstaka spår av förhistoriska aktiviteter.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med utredningen var att undersöka om området innehåller omarkerade fornlämningar.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Stenålderslämningar i Ledberg
Keywords: stone age; stenålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive